2009
DOI: 10.1088/1475-7516/2009/05/002
|View full text |Cite
|
Sign up to set email alerts
|

Grid based linear neutrino perturbations in cosmologicalN-body simulations

Abstract: We present a novel, fast and precise method for including the effect of light neutrinos in cosmological N -body simulations. The effect of the neutrino component is included by using the linear theory neutrino perturbations in the calculation of the gravitational potential in the N -body simulation. By comparing this new method with the full non-linear evolution first presented in [1], where the neutrino component was treated as particles, we find that the new method calculates the matter power spectrum with a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
178
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(186 citation statements)
references
References 22 publications
5
178
0
3
Order By: Relevance
“…The widely used phenomenological calculation of the nonlinear matter power spectrum called the HALOFIT (Smith et al 2003) has not been calibrated for models with massive neutrinos. Consistent treatments of massive neutrinos in the nonlinear structure formation using cosmological perturbation theory (Saito et al 2008(Saito et al , 2009Wong 2008;Lesgourgues et al 2009;Shoji & Komatsu 2009) and numerical simulations (Brandbyge et al 2008;Brandbyge & Hannestad 2009) have just begun to be explored. More work along these lines would be necessary to exploit the information on the growth structure to constrain the mass of neutrinos.…”
Section: Neutrino Massmentioning
confidence: 99%
“…The widely used phenomenological calculation of the nonlinear matter power spectrum called the HALOFIT (Smith et al 2003) has not been calibrated for models with massive neutrinos. Consistent treatments of massive neutrinos in the nonlinear structure formation using cosmological perturbation theory (Saito et al 2008(Saito et al , 2009Wong 2008;Lesgourgues et al 2009;Shoji & Komatsu 2009) and numerical simulations (Brandbyge et al 2008;Brandbyge & Hannestad 2009) have just begun to be explored. More work along these lines would be necessary to exploit the information on the growth structure to constrain the mass of neutrinos.…”
Section: Neutrino Massmentioning
confidence: 99%
“…Saito et al 2008Saito et al , 2009Wong 2008;Brandbyge et al 2008;Brandbyge & Hannestad 2009;Viel et al 2010;Marulli et al 2011;Bird et al 2012;Carbone et al 2012;Hou et al 2014;Lesgourgues & Pastor 2012). The renewed interest is mainly driven by the large amount of cosmological data available today, which allow placing competitive limits on the neutrino mass-scale and hierarchy.…”
Section: Revival Of Neutrino Sciencementioning
confidence: 99%
“…More recently, Brandbyge et al (2008) described a simple method for including the effect of massive neutrinos in large-scale N-body simulations, using a hybrid TreePM approach, but neglecting all the hydrodynamics; their findings already showed that the suppression of power due to the presence of massive neutrinos is increased by nonlinear effects. Subsequently, Brandbyge & Hannestad (2009) modeled neutrinos as a fluid with a grid method, and pointed out the relative benefits and drawbacks of implementing the effects of neutrinos in the form of particles versus a grid-based implementation. In their code, the gravitational force due to neutrinos is calculated using the linearly evolved density distribution of the neutrinos in Fourier space.…”
Section: Particle Implementation Of Massive Neutrinosmentioning
confidence: 99%
“…Let the rms mass fluctuation within a sphere of radius r be σ M (r). The average linear overdensity δ 2 = ν 2 σ M (r 2 ) within a radius r 2 , under the condition that the mean linear overdensity within the smaller radius r 1 is equal to δ 1 = ν 1 σ M (r 1 ), can be calculated as ν 2 = γ 12 ν 1 , where 6) where j 1 is the spherical Bessel function. We use this equation to obtain the average linear overdensity profile around a halo.…”
Section: Mass Density Profilementioning
confidence: 99%
“…Apart from this linear effect, massive neutrinos are also expected to cluster around gravitationally collapsed dark matter haloes as their streaming velocities are reduced and become comparable to the velocity dispersions of the halos, thereby modifying the dark matter halo total mass density profile. Previous work has studied this non-linear neutrino clustering [4][5][6][7][8][9]. Here, we present a new calculation with updated parameters and a more realistic halo model.…”
Section: Introductionmentioning
confidence: 99%